Rehabilitating a Historical Coal Mine in Wangaloa, New Zealand ⎯ A Holistic Approach to Mine Closure - Stenhouse, PB; Evans, CM; Thomas, D (Mine Closure 2006: First International Seminar on Mine Closure, 2006)
Over the past two years Solid Energy (SENZ) has been actively assessing and addressing the effects that they currently have on the environment and making a significant investment in environmental improvements, rehabilitation projects and environmental research to address historical and ongoing environmental issues. These investments have been driven by the company’s commitment to its environmental policy, which states (NZSSES website, 2006) “Solid Energy’s overall environmental objective is for the cumulative result of all the activities we undertake to have a positive net effect on the New Zealand environment.” Solid Energy has been rehabilitating Wangaloa Mine with this mission statement in the forefront of their consciousness. The efforts to date, outlined below, document the implementation of this mission statement into current rehabilitation efforts at their historical coal mine in Wangaloa, New Zealand.